A population‐based study of the prevalence and risk factors of low‐grade Plasmodium falciparum malaria infection in children aged 0–15 years old in northern Tanzania. Issue 5 (1st April 2019) - Peprah, S.; Dhudha, H.; Ally, H.; Masalu, N.; Kawira, E.; Chao, C. N.; Genga, I. O.; Mumia, M.; Were, P. A.; Kinyera, T.; Otim, I.; Legason, I. D.; et al.
Abstract: Objectives: Northern Tanzania experiences significant malaria‐related morbidity and mortality, but accurate data are scarce. We update the data on patterns of low‐grade Plasmodium falciparum malaria infection among children in northern Tanzania. Methods: Plasmodium falciparum malaria prevalence (pfPR) was assessed in a representative sample of 819 children enrolled in 94 villages in northern Tanzania between October 2015 and August 2016, using a complex survey design. Individual‐ and household‐level risk factors for pfPR were elicited using structured questionnaires. pfPR was assessed using rapid diagnostic tests (RDTs) and thick film microscopy (TFM). Associations with pfPR, based on RDT, were assessed using adjusted odds ratios (aOR) and confidence intervals (CI) from weighted survey logistic regression models. Results: Plasmodium falciparum malaria prevalence (pfPR) was 39.5% (95% CI: 31.5, 47.5) by RDT and 33.4% (26.0, 40.6) by TFM. pfPR by RDT was inversely associated with higher‐education parents, especially mothers (5–7 years of education: aOR 0.55; 95% CI: 0.31, 0.96, senior secondary education: aOR 0.10; 95% CI: 0.02, 0.55), living in a house near the main road (aOR 0.34; 95% CI: 0.15, 0.76), in a larger household (two rooms: aOR 0.40; 95% CI: 0.21, 0.79, more than two rooms OR 0.35; 95% CI: 0.20, 0.62). Keeping a dog near or inside the house was positively associated with pfPR (aOR 2.01; 95% CI: 1.26, 3.21). pfPR was not associated with bed‐net use or indoor residual spraying. Conclusions: Nearly 40% of children in northern Tanzania had low‐grade malaria antigenaemia. Higher parental education and household metrics but not mosquito bed‐net use were inversely associated with pfPR.